Chronic antipsychotic treatment targets GIRK current suppression, loss of long-term synaptic depression and behavioural sensitization in a mouse model of amphetamine psychosis - Groos, Dominik; Zheng, Fang; Rauh, Manfred; Quinger, Benedikt; Kornhuber, Johannes; Müller, Christian P.; Alzheimer, Christian (Journal of Psychopharmacology, 2018)
BACKGROUND:: Antipsychotic drugs (APDs) are the mainstay of the pharmacological treatment of psychotic disorders like schizophrenia. While the clinical efficacy of APDs has long since been established, the neurobiological mechanisms underlying their therapeutic benefits are still not well understood. METHODS:: Here, we used an escalating amphetamine regimen to induce a psychosis-like state in mice. To achieve clinically relevant drug concentrations in amphetamine-pretreated mice, the typical APD haloperidol or the atypical APD olanzapine were chronically administered via subcutaneously implanted osmotic mini-pumps. RESULTS:: Demonstrating their therapeutic efficacy, both drugs dampened amphetamine-induced hyperlocomotion and restored normal behaviour in the light-induced activity test. Whole-cell recordings from dopaminergic neurons of the ventral tegmental area (VTA) in ex vivo brain slices revealed two pronounced aberrations associated with the psychosis-like state: Strongly enhanced spontaneous firing and a substantial loss of G protein-gated inwardly rectifying potassium (GIRK) current upon activation of GABAB receptors with baclofen. Chronic haloperidol and olanzapine restored normal firing and partially rescued the GIRK current response to baclofen. In ex vivo slices containing the nucleus accumbens, which receives a dopaminergic projection from the VTA, abrogation of long-term synaptic depression (LTD) and enhanced excitatory drive onto medium spiny neurons were identified as synaptic consequences of amphetamine-induced psychosis. Again, both alterations proved amenable to chronic APD treatment. CONCLUSION:: Our data provide evidence for aberrant neuronal function and plasticity in the mesolimbic dopamine system during an induced psychotic state and identify these alterations as targets of chronic APD treatment.
EVALuna2:35829